2007
DOI: 10.1111/j.1099-1123.2007.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Audit Committee Existence and Audit Committee Meeting Frequency on the External Audit: Perceptions of Australian Auditors

Abstract: This article examines the impact of audit committee existence, the frequency of audit committee meetings and the auditor's attendance at meetings on aspects of the external audit. Using an experimental design, we find that the audit committee, the frequency of committee meetings and the auditor's attendance at meetings are significantly associated with a reduction in perceived audit risk. The impact on audit efficiency and audit testing is perceived to be minimal. Manager and partner hours are greater when mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 29 publications
8
97
1
6
Order By: Relevance
“…Indeed, the board of directors and the audit firm represent control mechanisms of the leaders' actions which help check that the decisions taken match the shareholders' interests. Hence, the independence of the members of the audit firm and of the board of directors can be regarded as mediating mechanisms which help with the resolution of conflicts between the external auditors and the management (Stewart and Munro, 2007). Moreover, they are two factors that affect the ability of the external auditor to resist the pressures of the audited.…”
Section: Econometric Estimate Of the Model And Interpretations Of Thementioning
confidence: 99%
“…Indeed, the board of directors and the audit firm represent control mechanisms of the leaders' actions which help check that the decisions taken match the shareholders' interests. Hence, the independence of the members of the audit firm and of the board of directors can be regarded as mediating mechanisms which help with the resolution of conflicts between the external auditors and the management (Stewart and Munro, 2007). Moreover, they are two factors that affect the ability of the external auditor to resist the pressures of the audited.…”
Section: Econometric Estimate Of the Model And Interpretations Of Thementioning
confidence: 99%
“…However, they did not find a significant correlation between the independence and financial expertise of audit committee members and the audit fee. Stewart and Munro (2007), using an experimental design, found that participants expect audit committees to increase audit fees, particularly when meetings are more frequent and the external auditor has to attend the meetings.…”
Section: Background and Audit Fee Researchmentioning
confidence: 99%
“…Using an experimental design, Stewart & Munro (2007) found that the audit committee's frequency of committee meetings and the auditor's attendance at meetings are significantly associated with a lessening in perceived audit risk. The impact on audit efficiency and audit testing seems to be nominal.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%